HUBUNGAN KEADILAN PROSEDURAL TERHADAP KEPERCAYAAN ORGANISASI - Ilham Hadisa; Donal Devi Amdanata (AMNESIA (JURNAL MANAJEMEN SUMBER DAYA MANUSIA), 2023)
The research method employed a literature study (library research), involving the collection of data from various literature related to the research topic. The research findings indicate that procedural justice by management positively contributes to employee trust. Employees who believe in procedural justice tend to have high organizational trust. The conclusion of this research provides a valuable contribution to the field of management, particularly in leadership, organizational behavior, and human resource management. The research findings also offer insights for organizational management in designing strategies to prevent behaviors that could undermine organizational trust. The results of this research highlight the crucial role of leadership in shaping positive attitudes and behaviors among employees in the organizational context.